Homosexuality and manliness in postwar Japan - Mackintosh, Jonathan D. (Routledge contemporary Japan series., 2010)
This book examines the history of the relationship between male homosexuality and conceptions of manliness in postwar Japan. It provides a detailed account of the formative years of the homo magazine genre in the 1970s, and explores its evolution in subsequent years, analyzing key issues including homophobia; gay liberation; male-male sex, love and friendship; the masculine body; and manly identity.